THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON LECTURER PERFORMANCE: A QUANTITATIVE STUDY IN HIGHER EDUCATION - LusyTunik Muharlisiani, Yoyok Soesatyo, AmroziKhamidi, Citrawati Jatiningrum, Siti Bariroh, JohnySugiono, Karwanto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Transformational leadership is a dire need for improving the performance of universities today. The model of transformational leadership is critical increasing the self-confidence of subordinates which will affect the increase in lecturer performance. This research aims to investigation the impact of the transformational leadership on lecturer performance. The method of exploration is quantitative examination, by circulating multifaceted authority polls (MLQ Form 5X) which an exploration instrument to gather information with purposive sampling procedure of 370 state lecturers in Surabaya. Statistic quantitative that utilizing graphic factual strategies to test the immediate impact between the factors with the Structural Equation Model. The main findings reveal that leadership has a significant impact on lecturer performance. The result on this study also groundbreaking initiative on each measurement of lecturer performance (productivity, work quality; initiative, teamwork, motivation; problem-solving, pressure; effective work; needs supervision and interpersonal impact). The discoveries of this examination uncover that transformational leadership lead improving the lecturer performance with groundbreaking authority positively affects instructor execution. Keywords:Lecturer performance, Transformational leadership, Higher Education